Ushul fiqh jilid I - H. Amir Syarifuddin (Logos, 1997)
Oen, Jil.I=C.1-3/oen, Jil.I=C.4/oen jil.I=c.5/ir, jil.1c.6-7/oen, Jil.I=c.8-9/ir,jil.1,c.10-12/oen, jil.I=c.13-14,Jil.1,c.15/ast c.16/ir,jil.1,c.17/ast jil.1=c.18,ws.c.19/tr,c.20-21/en, c.22